The role of spatial and temporal deixis in enhancing narrative understanding in Die Sommer - Megawati, Sri; Triyono, Sulis; Rikfanto, Aditya (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This study investigates how spatial and temporal deixis shape readers’ understanding of Ronya Othmann’s Die Sommer (2020), a novel alternating between German and Kurdish settings and perspectives. A qualitative analysis of deictic expressions identifies forms of spatial deixis (e.g., specific place names; vertical references like “sits on the floor” vs. “starry sky above”; and dynamic movements) and temporal deixis (e.g., historical years, seasonal markers, tense shifts, and temporal adverbs). Results show spatial deixis anchors Leyla’s story in intercultural spaces, guiding reader orientation and evoking her bicultural identity amid historical conflict. Temporal deixis places events in the general political and historical context, linking personal biography to collective memory. This study presents deixis as a narrative device that enables deeper reader involvement in a transcultural storyworld. By integrating Bühler’s and Ehlich’s deixis theories with narrative analysis, it contributes to understanding narrative structure, complex intercultural dynamics, and multiple cultural perspectives in contemporary transcultural literature and narratives.